2022
DOI: 10.3390/cancers14163991
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of Neuroendocrine Neoplasms: Any Role for the Chimeric Antigen Receptor T Cells?

Abstract: Neuroendocrine neoplasms (NENs) are a heterogeneous group of tumors with variable clinical presentation and prognosis. Surgery, when feasible, is the most effective and often curative treatment. However, NENs are frequently locally advanced or already metastatic at diagnosis. Consequently, additional local or systemic therapeutic approaches are required. Immunotherapy, based on chimeric antigen receptor T cells (CAR-T), is showing impressive results in several cancer treatments. The aim of this narrative revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Great improvements have been realized in MTC therapy with the availability of oral tyrosine kinase inhibitors, vandetanib and cabozantinib, as well as several other options proposed within clinical trials including everolimus and pasireotide and immunotherapies. Nevertheless, the therapeutic algorithm in patients with progressive disease is debated, as well as the timing of starting systemic therapies [ 4 , 5 , 6 , 7 ]. Biomarkers in MTC, as in other cancer types, are needed for several purposes including diagnostic screening, the early detection of disease recurrence and progression, the assessment of therapeutic response and prognostic evaluation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Great improvements have been realized in MTC therapy with the availability of oral tyrosine kinase inhibitors, vandetanib and cabozantinib, as well as several other options proposed within clinical trials including everolimus and pasireotide and immunotherapies. Nevertheless, the therapeutic algorithm in patients with progressive disease is debated, as well as the timing of starting systemic therapies [ 4 , 5 , 6 , 7 ]. Biomarkers in MTC, as in other cancer types, are needed for several purposes including diagnostic screening, the early detection of disease recurrence and progression, the assessment of therapeutic response and prognostic evaluation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is the best option when feasible, but a wide spectrum of systemic therapy is available for locally advanced or metastatic disease and includes somatostatin analogues (SSAs), molecular targeted therapy with everolimus and sunitinib, peptide receptor radionuclide therapy (PRRT) and chemotherapies (with different drugs such as capecitabine and temozolomide). In addition, promising data are emerging about a potential role of immunotherapy, mainly in combination with other immune check point inhibitors or with chemotherapy, in specific settings [8][9][10][11]. The goal of treatment is to improve patients' outcomes, considering toxicities and quality of life [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the original articles presented, this Special Issue includes a selection of timely review articles that provide comprehensive insights into the latest advancements. Fanciulli et al [ 12 ] conducted a meticulous analysis of pre-clinical and clinical data concerning CAR T cell therapy in neuroendocrine neoplasms, highlighting its promising potential in clinical practice. Choudhary et al [ 13 ] discussed the metabolic alterations observed in glioblastoma tumor cells, which have been investigated as contributing factors to immunosuppression and resistance against immunotherapies.…”
mentioning
confidence: 99%